Peran Vital Pendidikan Anak dan Dukungan Komunitas dalam Membangun Masa Depan Desa Karanganom - Ahmad Sokib; Fatimah Nadia Qurrota A’yun (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesia's national development, based on Pancasila, aims to create a just and prosperous society with education as a key focus. In Karanganom Village, children's education is crucial despite challenges related to infrastructure and facilities. Active community involvement, including parental roles and additional programs such as Qur'an reading guidance, significantly improves educational quality. Family education is also vital for shaping children's character through habits and improvisation. Support from the community and local organizations like IPSENA enhances children's learning enthusiasm. However, challenges such as teacher shortages and time management issues need to be addressed with creative solutions and community cooperation for optimal educational outcomes.